Bee-cause - Designing to receive: a project which explores designing landform and soils to receive and support a variety of flowering species in strategically located corridors; bridging the boundary between the cape honey bee foraging grounds and bee pollinated farmlands, as a result creating other socioeconomic, educational and environmental relationships - Lubbe, Roux (School of Architecture, Planning and Geomatics, 2018)
"Land Mosaic" is a term often referred to by Richard Forman as the fundamentally different ecotopes which play out within a landscape forming a spatial juxtaposition of landscape patchworks. Each ecotope is defined by a variety of factors such as landform, soils, hydrology and weather. In a natural setting, the relationship between two different ecotopes tend to be less abrupt than that of an urban setting. When two different ecotopes meet, a gradual gradient is formed called an Ecotone. A sort of "mosaic" or gradient of ecotopes entwined within the boundary of the ecotone. Gradient is a critical characteristic of many healthy ecotope edges. In the book "Urban Ecology" by R. Forman a comparison is made between this ecological theory and the functioning of an urban setting. This study uses Formans theory in Section A. to analyse the zoning, land use and function of the urban fabric within the diverse neighbourhood of Elsieskraal, CT, following the rapid changing zones along the public river corridor, to reveal relationships between the spatial qualities of ecotope boundaries and the success of the ecotopes functioning. The study finds an interesting process is hindered by an unconventional boundary, perhaps the type of boundary a city planning or urban design method of analysis might have overlooked. The process of crop pollination by Cape honey bees (Apis mellifera capensis). The study found that although no physical conventional barrier stops the bees from flying into the desired agricultural land from their more permanent foraging grounds, they are restricted by the spatial quality of the two ecotopes edges. The lack of curve linear "lobed" edges prevent the interaction between the two ecotopes through short flight range by the bees. In Section B. the document further continues to investigate the process of pollination, bee life cycle and desired nectar-rich plant palette to design system which encourages the interaction whilst assisting the devastating bee crises, increase crop yield. The design lays out a network of proposed corridors in a specific off-set from one another, running through the agricultural land, linking schools environmental, tourism and economic activities as a "spin-off" effect. Emphasis is placed on designing landform and soils within the network of corridors to help grow the largest variety of colourful, nectar abundant and scented flowering species possible, all which are carefully chosen for their desire by the cape honey bee and their flowering time in comparison to local crops. By the morphing the boundary of nectar-rich foraging grounds into the mono-cultural farm land in the form of lobes the project creates an essential relationship between crop and foraging ground, reintroducing a critical process of pollination and bridging the boundary between socioeconomic and environmental aspects.